2020
DOI: 10.3390/plants10010044
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma longa L. Rhizome Essential Oil from Extraction to Its Agri-Food Applications. A Review

Abstract: Curcuma longa L. rhizome essential oil is a valuable product in pharmaceutical industry due to its wide beneficial health effects. Novel applications in the agri-food industry where more sustainable extraction processes are required currently and safer substances are claimed for the consumer are being investigated. This review provides information regarding the conventional and recent extraction methods of C. longa rhizome oil, their characteristics and suitability to be applied at the industrial scale. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 219 publications
(278 reference statements)
2
42
0
Order By: Relevance
“…There is also an increasing interest in curcumin oil for its protective roles in cardiovascular disorders by lowering the total blood cholesterol and low-density lipoprotein levels [ 15 ]. The essential oil extracted from the rhizomes of Curcuma longa has been reported to have favorable characteristics for human consumption [ 16 ]. Self-nanoemulsifying drug delivery system (SNEDDS) is a promising approach to enhance the absorption of poorly water-soluble drugs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also an increasing interest in curcumin oil for its protective roles in cardiovascular disorders by lowering the total blood cholesterol and low-density lipoprotein levels [ 15 ]. The essential oil extracted from the rhizomes of Curcuma longa has been reported to have favorable characteristics for human consumption [ 16 ]. Self-nanoemulsifying drug delivery system (SNEDDS) is a promising approach to enhance the absorption of poorly water-soluble drugs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several investigations carried out with the main components in plants of this family have demonstrated their antioxidant capacity against the DPPH radical in comparison with Trolox and ascorbic acid-among the most important ones are α-turmerone, β-turmerone, and Ar-turmerone [62]. In an investigation to evaluate the hepatoprotective effect of an extract of Amomum cardamomum on carbon-tetrachloride-induced liver damage through antioxidant activity in rats, it was found to possess significant hepatoprotective activity on acute liver injury, which could be derived from its antioxidant properties and the decrease of liver cytochrome P450 [63].…”
Section: Discussionmentioning
confidence: 99%
“…It also has beneficial effects on several chronic disease states linked with inflammation and oxidative stress, as observed in DM and cancer [112]. Recently, it was reported that CUR inhibits the COVID-19 protease enzyme [113]. One proposed mechanism of CUR ameliorating DM is related to its antihyperlipidemic activity via suppression of fatty-acid synthase, carnitine palmitoyltransferase 1, 3-hydroxy-3-methyl glutaryl coenzyme A reductase, and acyl-CoA cholesterol acyltransferase enzymes [114].…”
Section: Curcumin (Cur)mentioning
confidence: 99%